The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1002/(sici)1097-0142(19961101)78:9<1935::aid-cncr14>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Type of human papillomavirus is related to clinical features of cervical carcinoma

Abstract: These data suggest that the HPV type present in cervical carcinoma is related to clinical behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
47
1

Year Published

1998
1998
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 32 publications
6
47
1
Order By: Relevance
“…Current data regarding the relationship between HPV-18 and histologic type are in line with those reported by others. 25,26 Although HPV-16 remained the most common HPV infection in both SCC and AC, our data demonstrate that HPV-18 has a significant association with AC. This finding may reflect the fact that different virus receptors exist in cervical cells with different morphologic potentials, or it may indicate that specific HPV infection actually plays a role in directing carcinogenesis.…”
Section: Resultsmentioning
confidence: 62%
“…Current data regarding the relationship between HPV-18 and histologic type are in line with those reported by others. 25,26 Although HPV-16 remained the most common HPV infection in both SCC and AC, our data demonstrate that HPV-18 has a significant association with AC. This finding may reflect the fact that different virus receptors exist in cervical cells with different morphologic potentials, or it may indicate that specific HPV infection actually plays a role in directing carcinogenesis.…”
Section: Resultsmentioning
confidence: 62%
“…[12][13][14][15][16][17] The presence of HPV type 18 has been identified as a predictor of early recurrence and poor survival. [5][6][7][8] A recent study found improved survival in patients with HPV 58 positive tumors. 33 The impact of multiple HPV infection, however, was not investigated.…”
Section: Discussionmentioning
confidence: 99%
“…32 According to the manufacturer's information, the biotinylated type-specific ISH probes were selected for minimal cross-hybridization with other HPV-types. Using non-radioactive Southern blot hybridization at high stringency against 100 ng of cloned HPV DNA from types 6,11,16,18,30,31,33,35,45, 51 and 52 these probes were specific for HPV 16, 18, 31 and 33, respectively, without cross-reaction with the other HPV-types. These probes did also not react with normal human nuclear DNA when probed by ISH, or with E. coli DNA when tested by dot blot hybridization.…”
Section: In Situ Hybridizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, controversial data have been reported concerning the prognostic value of the HPV genotype associated with invasive carcinoma. A favourable outcome of tumours associated with HPV31 7 or HPV58 8 and an unfavourable outcome of tumours associated with HPV31 7,8 and a unfavourable outcome of tumours associated with HPV18 were reported, [9][10][11][12] whereas no significant association was observed in other studies. 13,14 In this context we have performed a virological and clinical retrospective study with a long-term follow up in order to (i) define the HPV types found in a large series of invasive carcinoma in France and (ii) assess the prognostic value of the different HPV types.…”
mentioning
confidence: 81%